Search
Ask a question
0

what's the inverse of f(x)=-(x-2)^1/2+4

what's the inverse of f(x)=-(x-2)^1/2+4

3 Answers by Expert Tutors

Tutors, sign in to answer this question.
ROGER F. | DR ROGER - TUTOR OF MATH, PHYSICS AND CHEMISTRYDR ROGER - TUTOR OF MATH, PHYSICS AND CH...
4.9 4.9 (127 lesson ratings) (127)
0
Write y, instead of f(x), then for an inverse, exchange x and y,

So we get:    x = -(y – 2 )^1/2  + 4

                 x - 4 = -(y – 2 )^1/2   

multiply by – 1:

                4 – x = (y – 2 )^1/2   

Square both sides:

          (4 – x)^2   = y – 2

FOIL: 16 – 8x  + x^2  = y – 2

SO:             y    =    x^2  – 8x  + 16  or  y  =  (x – 4)^2
Vivian L. | Microsoft Word/Excel/Outlook, essay composition, math; I LOVE TO TEACHMicrosoft Word/Excel/Outlook, essay comp...
3.0 3.0 (1 lesson ratings) (1)
0
Hi Rich;
f(x)=-(x-2)^1/2+4
y=-(x-2)1/2+4
Let's subtract 4 from both sides...
y-4=-(x-2)1/2+4-4
y-4=-(x-2)1/2
Let's multiply both sides by -1...
-1(y-4)=(-1)[-(x-2)1/2]
4-y=(x-2)1/2
Let's square both sides...
(4-y)2=[(x-2)1/2]2
(4-y)2=x-2
Let's FOIL the left side...
FIRST...(4)(4)=16
OUTER...(4)(-y)=-4y
INNER...(-y)(4)=-4y
LAST...(-y)(-y)=y2
y2-8y+16=x-2
Let's add 2 to both sides...
y2-8y+16+2=x-2+2
y2-8y+18=x
Let's switch x and y...
x2-8x+18=y
x2-8x+18=f-1(x)
 
 
Steve S. | Tutoring in Precalculus, Trig, and Differential CalculusTutoring in Precalculus, Trig, and Diffe...
5.0 5.0 (3 lesson ratings) (3)
0
When doing inverses be sure to find the domain and range of the original function. They will become the range and domain of the inverse, respectively.

In this case the original function is the BOTTOM HALF of a horizontal parabola. It’s inverse will be the LEFT SIDE of a vertical parabola. (Do quick sketches using transformations of f and then reflecting over y = x. See GeoGebra sketch here:
http://www.wyzant.com/resources/files/263815/inverse_of_a_square_root_function)

Domain of f: x-2 >= 0, x >= 2
Range of f: y <= 4

Range of f^(-1): y >= 2
Domain of f^(-1): x <= 4

Let g(x) = f^(-1)

x = -(g - 2)^(1/2) + 4

x-4 = -(g - 2)^(1/2)

(x-4)^2 = g - 2

g(x) = f^(-1)(x) = (x-4)^2 + 2, x <= 4